Perbedaan Persepsi Antara Mahasiswa Senior Dan Junior Mengenai Profesi Akuntan Pada Program S-1 Reguler Fakultas Ekonomi Universitas Lancang Kuning - kamilah, faizah (Jurnal Daya Saing, 2017)
This Research aimed to see whether there are differences in perception between senior and junior students of the accounting profession in the S-1 Regular program. The results showed that the S-1 Regular program, senior students perceptions of the "accountant as a profession" is lower than the junior student perceptions. The results showed that the more senior they (the longer they follow accounting education), the more they do not like accounting and increasingly do not want a career and worked as an accountant. Keywords:Professional responsibility. Integrity, objectivity, competence, confidentiality